Operative Dictations in Orthopedic Surgery - Saghieh, Said.; Weinstein, Stuart L.; Hoballah, Jamal J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Operative Dictations in Orthopedic Surgery is a valuable resource for teaching orthopedic surgical trainees and practicing orthopedic surgeons how to document their operative procedures. The book  includes the majority of the commonly performed orthopedic procedures. For each procedure, a list of common indications is given, covering 95% of the situations in which particular procedures will be used, as well as a list of essential steps. This is then followed by a list intended to prompt the surgeon for particular details to note and dictate within the template, a list of possible complications that are typically associated with a particular surgical procedure,  and templates of operative dictation that allow the surgeon to individualize their dictations. Ample space is also provided to allow each surgeon to add notes. Concise and easy to use, Operative Dictations in Orthopedic Surgery is a unique tool for orthopedics surgical residents and residents in practice that better prepares them to participate actively and learn as much as possible in the operating room.
Posterior Spinal Fusion with Instrumentation -- In Situ Fusion L5 to S1 -- Open Reduction of DDH (Medial Approach) -- Salter Innominate Osteotomy -- Pemberton Osteotomy -- Acetabular Shelf -- Percutaneous Epiphyseodesis -- Proximal Femoral Osteotomy -- Hamstring Lengthening -- Tibia Spike Osteotomy for Genu Varum -- Closed Manipulation and Tenotomy for Clubfoot -- Posteromedial Release for Clubfoot -- Anterior Tibialis Transfer to the Lateral Cuneiform -- Split Posterior Tibial Tendon Transfer -- In Situ Pinning of SCFE -- Closed Reduction and Percutaneous Pinning of Supracondylar Humerus Fracture -- Open Reduction and Internal Fixation of Supracondylar Humerus Fracture -- Laminotomy and Partial Discectomy for Lumbar Disc Herniation -- Central Lumbar Decompression -- Posterolateral Interspinal Fusion with Pedicle Screws -- Lumbar Anterior Decompression and Fusion with Cage (L2-5) -- Anterior Cervical Decompression and Fusion -- Vertebroplasty -- Cervical Laminoplasty -- Hybrid Total Hip Arthroplasty -- Primary Uncemented Total Hip Arthroplasty -- Revision Hip Arthroplasty -- Core Decompression -- Femoral Antegrade IM Nail -- Femoral Neck Fracture Closed Reduction and Percutaneous Multiple Screw Fixation -- Intertrochanteric Open Reduction and Internal Fixation with Dynamic Hip Screw -- Percutaneous Sacroiliac Joint Screw Fixation -- Supracondylar Femur Open Reduction and Internal Fixation -- Bipolar Hemi-Arthroplasty -- Iliac Crest Bone Graft (Anterior) -- Primary Total Knee Arthroplasty -- Medial Unicompartmental Knee Replacement -- Distal Femoral Varus Osteotomy -- High Tibial Osteotomy (Closing Wedge) -- Medial Opening Wedge Tibial Osteotomy -- Arthroscopic Meniscectomy of the Knee -- ACL Reconstruction -- Anteromedial Tibia Tubercle Transfer -- Lateral Retinacular Release -- Chronic/Exertional Compartment Syndrome Release -- Tibia Intramedullary Nail -- Meniscus Repair -- Standard below Knee Amputation -- Tibia Shaft Angular Deformity Correction by TSF -- Mini-Invasive Primary Total Knee Arthroplasty -- Open Reduction and Internal Fixation of Tibial Plateau Fractures -- Hallux Valgus- Proximal Ludloff Osteotomy -- Distal Chevron Osteotomy with Capsulorrhaphy -- Hammer Toe Correction -- Rheumatoid Foot Reconstruction -- Repair of Acute Achilles Tendon Rupture -- Ankle Fusion -- Subtalar Fusion -- Triple Arthrodesis:  Fusion of the Subtalar, Calcaneocuboid, and Talonavicular Joints -- Total Ankle Replacement -- Tarsal Coalition Resection -- Lateral Ankle Ligament Reconstruction – Brostrom Type -- Distal Tibia Fracture:  Non Bridging Hybrid External Fixator -- Ankle Fracture – Open Reduction and Internal Fixation -- Lisfranc Open Reduction and Internal Fixation -- Talus Open Reduction and Internal Fixation -- Diagnostic Shoulder Arthroscopy -- Arthroscopic Acromioplasty -- Arthroscopic Rotator Cuff Repair -- Arthroscopic Bankart Repair -- Open Bankart Repair -- Weaver-Dunn Acromioclavicular Reconstruction -- Inferior Capsular Shift -- Mini-Open Rotator Cuff Repair -- Large Rotator Cuff Repair – Open -- Total Shoulder Replacement -- Open Reduction and Internal Fixation Three-Part Proximal Humerus Fracture -- Closed Reduction and Pinning of Two Part Proximal Humerus Fracture -- Hemiarthroplasty of Shoulder -- Antegrade Intramedullary Nailing: Humerus Shaft Fractures -- Biceps Tenodesis -- Distal Humerus Open Reduction and Internal Fixation -- Elbow Arthroscopy -- Subcutaneous Ulnar Nerve Transposition -- Both Bone Forearm Fracture Open Reduction and Internal Fixation -- Distal Radius External Fixation and Percutaneous Pinning -- Open Reduction and Internal Fixation Distal Radius, Volar Approach -- Wrist Fusion -- Wrist Arthroscopy -- Percutaneous Scaphoid Fixation -- Treatment of Scaphoid Non-Union -- Volar Ganglion Excision -- Dorsal Ganglion Excision -- Release De Quervain -- Congenital Trigger Thumb Release -- Trigger Finger Release -- Flexor Tendon Repair -- Extensor Repair -- CMC Ligament Reconstruction and Tendon Interposition -- Carpal Tunnel Release: Open Technique -- Digital Nerve Epineurial Repair -- Swan Neck Deformity Reconstruction -- Flexor Digitorum Superficialis PIP Tenodesis -- Boutonnière Deformity: PIP Joint Arthroplasty -- Open Reduction and Internal Fixation of Unicondylar Phalangeal Fractures:  Screw Fixation -- Tendon Transfers for Radial Nerve Palsy -- Curettage and Grafting of a Cystic Bone Lesion -- Incisional Biopsy – Soft Tissue -- Incisional Biopsy – Bone Tumor.
Keywords: Surgery; Orthopedics; General Surgery; Surgical Orthopedics